PRARANCANGAN PABRIK MONOKLOBENZENE DARI BENZENE DAN KLORIN KAPASITAS 35000 TON/TAHUN - , BHINARTA WINDU S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Monochlorobenzene (C6H5Cl) is the result of the chlorination of benzene by reacting chlorine gas and benzene, with the help of a catalyst ferrychloride in bubble stirred reactor at inlet temperature of 80â°C and a pressure of 2 atm. The heat of reaction that arises was taken with the cooling water flowing through the coil that was placed inside reactor. The liquid reaction products that still contain the catalyst is neutralized in the decanter. Then lighter fluid phase decant distilled to obtain the results monochlorobenzene out at the top of the tower recycle, while the bottom of the distillation tower-01 as much as 5163.0398 kg/hour, as much dichlorobenzene 748,8478 kg/hour, and 99% yield of 99% monochlorobenzene out at the top of the distillation tower-02 at 4419,1919 kg/hour. Hydrochloric acid out of the absorber 5076,9616 kg/hour. The plant has capacity of 35000 ton/year and is established in Cilegon,Banten on an area of 6 hectares, including residential and extension. Fixed capital of Rp243.614.046.621,95 , working capital of Rp 67.917.460.740,79 , percent return of investment before tax of 33,43% and 16,72% after tax. Break even point is 48.13% and 25.42% shut down point. It can be concluded that this plant is feasible for further study.